The Development of Science Learning Media Based on Discovery Learning Assisted by Canva on Electricity Material for Students of SMP Negeri 7 Muaro Jambi - Aurel, Novita Sari; Syefrinando, Boby; Sastradika, Dedi (Science and Mathematics Education Journal, 2025)
This research article aims to develop science learning media based on discovery learning using Canva and measure its affect on understudy learning results. This investigate employments inquire about and improvement (R&D) strategy utilizing the ADDIE (Analyze, Plan, Create, Actualize, Assess) show. The product validation results place the media developed in the "very good" category with an average media expert validation value of 4.54 and an average content expert validation value of 4.8. Discovery Learning-based learning media is proven to have a very high level of practicality, with teachers giving an assessment of 69.2% (practical) and students giving an assessment of 80% (very practical). The overall average is 74.6%, indicating that the media is effective in supporting learning. The students' average pretest score was 41.47, which increased significantly to 82.31 after the intervention. The t-test results obtained a T value of 26.227 and a P value of 0.000, which shows that there is a significant difference between the pretest and posttest results. However, this study was limited to 32 students, which may limit the generalizability of the results to similar situations and populations.